FAKTOR-FAKTOR KEAKTIFAN KADER DALAM KEGIATAN POSYANDU DI WILAYAH KERJA PUSKESMAS BETUNGAN KOTA BENGKULU - Royani, Ida (UNIVED Press, Universitas Dehasen Bengkulu, 2018)
IHC is a community service post, which is one of the community-based health effort managed and organized from, by, for and with the community, the decline becomes inactive cadres in IHC activities may lead to the ineffectiveness of service. The purpose of this study was to determine the factors associated with the activeness of cadres in the IHC of Betungan Health Center in the city of Bengkulu in 2017. The design study used was an observational analytic cross sectional approach, this study was conducted in Betungan health center in Bengkulu on March 11 to June 11, 2017. The study population were all cadres in Betungan health center Bengkulu, with the samples of 49 people taken by using a total sampling technique. The collection of data was done directly using the check list sheet, and analyzed using the chi-square test for the education and exacted fisher test used in the variable age and occupation. The results showed nearly all (87.8) aged 25-54, the majority (73.5) were less educated, almost all (87.8) did not work and almost all (87.8) were active cadres. The results of chi-square value of age (p = 0.01), education (p = 0.00) and work (p = 1.000). with the rate of 95%, if p <0.05 means that there was a relationship between age and education, and if this study p> 0.05 means that there was no relationship between the work with the cadres activeness in Betungan health center in Bengkulu.This study is expected to provide information about the factors associated with the activeness of the cadres in IHC activities to institutions of the clinic, cadres and researchers.